Influence of Flow Rate Variation On Bio-Energy Generation During Anaerobic Co-Digestion - Siddique, Md. Nurul Islam; Zularisam, A. W.; Mimi Sakinah, A. M. (Elsevier, 2015)
The anaerobic biodegradability of a combination of petrochemical wastewater (PWW) and thickened manure activated sludge (TMAS) was measured with a 4.5 l pilot-scale continuous stirred tank reactor, ran at mesophilic (37 8C) condition. The anaerobic digestion, biogas generation, and energy assessment were analyzed for ten Ã¯Â¬Âow rates; 170, 220, 300, 370, 410, 475, 540, 600, 640 and 680 ml/day at mesophilic condition (37 8C). The analytical data revealed that the environmentally complied optimum Ã¯Â¬Âowratewas370ml/day,forbio-energygeneration.